Perbedaan Pengaruh Terapi Bermain Mewarnai Gambar dengan Bermain Puzzle Terhadap Kecemasan Anak Usia Prasekolah di IRNA Anak RSUP Dr.M.Djamil Padang : Difference in the Effects of Coloring Play Therapy by Playing Puzzles Against Children's Anxiety Preschool at IRNA Children's Hospital Dr.M.Djamil Padang - Elza Sri Pratiwi; Deswita (Fakultas Keperawatan Universitas Andalas, 2013)
Illness and hospitalization are stressors that cause anxiety in children. The non-pharmacological management such as coloring pictures and play puzzle can be an alternative to reduce the anxiety. The purpose of this study was to determine differences in anxiety scores in hospitalized preschool children before and after coloring pictures and play puzzles. This study used a quasi-experimental design with non-equivalent comparison group pretest-posttest design, with 30 respondents sepatarated in two groups. Data collected using questionnaires. The results showed that there were significant differences in anxiety scores decreased in both groups (p=0.010/<α), and coloring pictures reduce more anxiety scores compared with puzzle play (mean difference=5.93points). The conclusion of this resesearch showed that both coloring pictures and play puzzle therapy can reduce anxiety scores. Play therapy coloring pictures better than the puzzle play therapy in reducing anxiety scores. It is recommended to health care institutions to improve health care for children again by giving therapeutic preschool coloring pictures to play especially on a regular basis to reduce anxiety in preschool children.